Inherited human group IVA cytosolic phospholipase A2 deficiency abolishes platelet, endothelial, and leucocyte eicosanoid generation. Issue 11 (17th October 2016) - Kirkby, Nicholas S.; Reed, Daniel M.; Edin, Matthew L.; Rauzi, Francesca; Mataragka, Stefania; Vojnovic, Ivana; Bishop‐Bailey, David; Milne, Ginger L.; Longhurst, Hilary; Zeldin, Darryl C.; Mitchell, Jane A.; Warner, Timothy D.
ABSTRACT: Eicosanoids are important vascular regulators, but the phospholipase A2 (PLA2 ) isoforms supporting their production within the cardiovascular system are not fully understood. To address this, we have studied platelets, endothelial cells, and leukocytes from 2 siblings with a homozygous loss‐of‐function mutation in group IVA cytosolic phospholipase A2 (cPLA2 α). Chromatography/mass spectrometry was used to determine levels of a broad range of eicosanoids produced by isolated vascular cells, and in plasma and urine. Eicosanoid release data were paired with studies of cellular function. Absence of cPLA2 α almost abolished eicosanoid synthesis in platelets ( e.g., thromboxane A2, control 20.5 ±1.4 ng/ml vs. patient 0.1 ng/ml) and leukocytes [ e.g., prostaglandin E2 (PGE2 ), control 21.9 ± 7.4 ng/ml vs. patient 1.9 ng/ml], and this was associated with impaired platelet activation and enhanced inflammatory responses. cPLA2 α‐deficient endothelial cells showed reduced, but not absent, formation of prostaglandin I2 (prostacyclin; control 956 ± 422 pg/ml vs. patient 196 pg/ml) and were primed for inflammation. In the urine, prostaglandin metabolites were selectively influenced by cPLA2 α deficiency. For example, prostacyclin metabolites were strongly reduced (18.4% of control) in patients lacking cPLA2 α, whereas PGE2 metabolites (77.8% of control) were similar to healthy volunteer levels. These studies constitute a definitive account, demonstrating the fundamental role of cPLA2 α to eicosanoid formation and cellular responses within the human circulation.—Kirkby, N. S., Reed, D. M., Edin, M. L., Rauzi, F., Mataragka, S., Vojnovic, I., Bishop‐Bailey, D., Milne, G. L., Longhurst, H., Zeldin, D. C., Mitchell, J. A., Warner, T. D. Inherited human group IVA cytosolic phospholipase A2 deficiency abolishes platelet, endothelial, and leucocyte eicosanoid generation. FASEB J. 29, 4568‐4578 (2015). www.fasebj.org